Growth and Production of Sweet Corn (Zea mays var. Saccharata Sturt.) at Various Doses of Micro Inorganic Fertilizers (3.14% Zn – 2.54% Cu) - Mulyana, Erik; Rosyad, Astryani; Furqoni, Hafith; Khairullah, Adrian; Annas, Sofian; Suwarto, Suwarto (Buletin Agrohorti, 2025)
Sweet corn is a horticultural commodity that is widely cultivated in Indonesia. This study aimed to determine the development and growth response of sweet corn plants to the application of different doses of micro inorganic fertilizer (3.14% Zn – 2.54% Cu). The research was conducted at Sindangbarang Experimental Field, Bogor, West Java. This experiment used a Randomized Complete Block Design (RCBD) with a single factor, namely the dose of fertilizer application. Treatments were arranged in 4 levels of application, namely: (1) control, (2) standard NPK, (3) NPK + 1 micro dose, (4) ¾ NPK + 1 micro dose. The results of this test indicate that the application level of micro inorganic fertilizers at the application level of NPK fertilizer + 1 micro dose and ¾ NPK + 1 micro dose fertilizer treatment can generally provide plant height, stem diameter, number of leaves, cob length, cob diameter, stover weight, cob weight with husk, cob weight without husk, production per plot, and productivity which were statistically higher than the control treatment. The application of NPK + 1 micro dose and fertilizer treatment of ¾ NPK + 1 micro dose have Relative Agronomic Effectiveness (RAE) values that meet the requirements to pass the fertilizer effectiveness test, with the highest RAE value obtained in the application of ¾ NPK + 1 micro dose fertilizer at 118%. Keywords: copper, effectivity of fertilizer, horticulture plants, zinc